A Machine Learning Approach in Autism Spectrum Disorders: From Sensory Processing to Behavior Problems - Alateyat, Heba; Cruz, Sara; Cernadas, Eva; Tubío-Fungueiriño, María; Sampaio, Adriana; González-Villar, Alberto; Carracedo, Angel; Fernández-Delgado, Manuel; Fernández-Prieto, Montse (Frontiers in Molecular Neuroscience, 2022)
Atypical sensory processing described in Autism Spectrum Disorders (ASD) frequently cascade into behavioral alterations: isolation, aggression, indifference, anxious/depressed states, or attention problems. Predictive machine learning models might refine the statistical explorations of the associations between them by finding out how these dimensions are relatedThis study investigates whether behavior problems can be predicted using sensory processing abilities. Participants were 72 children and adolescents (21 females) diagnosed with ASD, aged between 6 and 14 years (M = 7.83 years; SD = 2.80 years). Participants’ parents were invited to answer the Sensory Profile 2 (SP2) and the Child Behavior Checklist (CBCL) questionnaires. A collection of 26 supervised machine learning regression models of different families was developed to predict the CBCL outcomes using the SP2 scores. The most reliable predictions were for outcomes: total problems (using as inputs the items in the SP2 touch scale), anxiety/depression (using avoiding quadrant), social problems (registration), and externalizing scales, revealing interesting relations between CBCL outcomes and SP2 scales. The prediction reliability on the remaining outcomes was “moderate to good” excepting somatic complaints and rule-breaking, where it was “bad to moderate”. Linear and ridge regression achieved the best prediction for a single outcome and globally, respectively, and gradient boosting machine achieved the best prediction in three outcomes. Results highlight the utility of several machine learning models in studying the predictive value of sensory processing impairments (with an early onset) on specific behavior alterations, providing evidences of relationship between sensory processing impairments and behavior problems in ASD.